The nature and meaning of body concepts in everyday language and theoretical discourse - Pollio, Howard R.; Finn, Michael T.; Custer, Morgun (Journal of psycholinguistic research, 2016)
Within phenomenological philosophy four topics, (1) Body, (2) Time, (3) Others and the Social Order and (4) World serve as the major contexts in which human perception, action and reflection take place. At present only three of these domains have been studied from an empirical perspective, leaving Body as the one domain requiring further analysis. Given this state of affairs, the purpose of the present study is to determine the everyday and theoretical meanings of body. To accomplish this task participants coded randomly selected body- related words into groups on the basis of having similar meanings. Once these groupings were established they were then evaluated by statistical clustering and multidimensional scaling procedures. Results indicated that it was possible to define the everyday meaning of the human experience of the human body in terms of the following set of themes: (1) inside/outside, (2) visible/not visible, (3) vitality and activity, (4) instrument and object and (5) appearance and self-expression. Concerns about the representativeness of the words studied led to the development and use of individual word pools from which a set of 50 partially different words was randomly selected for each participant. Results indicated little difference between themes produced in the present study when compared with those of an earlier study. The specific themes derived from the present study were then related to embodiment issues as reflected in the philosophical writings of Merleau-Ponty, the psycholinguistic analyses of Lakoff and Johnson and experimental psychology.
Published online: 30 April 2015
Gesehen am 03.11.2020